Rethinking Stable Ischemic Heart Disease: Time for a Copernican Revision (Journal of Bangladesh College of Physicians and Surgeons, 2014)
DOI: http://dx.doi.org/10.3329/jbcps.v31i4.21000 Journal of Bangladesh College of Physicians and Surgeons Vol.31(4) 2013: 179-180